IMPLEMENTASI TRAINING EMOTIONAL SPIRITUAL QUOTIENT (ESQ) DI UNIVERSITAS ISLAM MAKASSAR - Badaruddin Kaddas; Mardyawati Yunus; Abdul Nangku (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
One of the obligations of every student at the Makassar Islamic University is to take part in the Emotional Spiritual Quotient (ESQ) Training. ESQ is a combination of EQ (Emotional Quotients) and SQ (Spiritual Quotients), which is a combination of emotional and spiritual intelligence control. The purpose of this study is to understand the implementation of ESQ Training and its effect on the behavior of students who have participated. This study found that the students of the Islamic Faculty of the Islamic University of Makassar had participated in the ESQ Training and attended the training process according to the schedule. The influence after training was initially felt to provide good benefits for mental and spiritual awareness, but felt only for a moment.